Efficacy and pH of glyphosate spray solutions after the addition of nitrogen fertilizers and the use of CO2-pressurized sprayer - Carvalho, Saul Jorge Pinto de; Damin, Virginia; Dias, Ana Carolina Ribeiro; Yamasaki, Gaspar Miura; Christoffoleti, Pedro Jacob (Pesquisa Agropecuaria Brasileira, 2010)
This work was developed with the objective of evaluating the efficacy and the pH of glyphosate spray solutions after the addition of nitrogen fertilizers and the use of CO2-pressurized sprayer. In field conditions, two rates of glyphosate (360 and 720 g ha-1) were applied either alone or combined with two concentrations of urea (2.5 and 5.0 g L-1) or ammonium sulfate (7.5 and 15.0 g L-1). In laboratory, the pH of the glyphosate solutions was measured after using different concentrations of the product and nitrogen fertilizers and after using a CO2-pressurized sprayer. For all field condition evaluations, the lowest glyphosate rate had higher biological efficacy after the addition of ammonium sulfate (15 g L-1) to the spray solution. Urea (5 g L-1) promoted benefits only at the 28th-day evaluation. In laboratory, the increase of glyphosate concentration promoted gradual acidification of the spray solution, which stabilized at pH 4.5. Ammonium sulfate caused minor acidification of the herbicide solution, whereas urea did not change the pH. The use of CO2-pressurized sprayer had small effect on the solution's pH. Highest glyphosate efficacy identified after the addition of nitrogen fertilizers has little relation with changes on the solution's pH.
Keywords: absorption; acidifi cation; herbicide spray; desiccation; ammonium sulfate; urea